2018
DOI: 10.26417/ejed.v1i1.p56-75
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Greek EFL Teachers Participation in Online Communities of Practice as a Means of Professional Development

Abstract: This paper examines EFL teachers' participation in online Communities of Practice (CoPs) and its impact on their professional development. The study focuses on 50 EFL teachers who became members of CoPs using an online platform named 2gather developed by the University of Athens in the context of a national in-service professional development project in Greece. Founded on the theory of situated learning, CoPs have been defined as "groups of people who share a concern, a set of problems, or a passion about a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…As the international educational policy increases expectations for improved educational outcomes, a more comprehensive understanding of teacher professional development experiences that can enhance their knowledge and can support teacher growth and change proves indispensable to policy decision makers and training course designers. Since traditional teacher professional development policies have been largely found to be ineffective, recent research findings confirm that online CoPs with their technological affordances and properly designed implementation schedules have a real potential to be an effective model for the professional development of teachers (Kourkouli, 2018). The present paper provides evidence in the direction of evaluating the effectiveness of this innovative teacher education model and highlighting this perspective in terms of the Coordinators' reports while recognizing their key role.…”
Section: Chart 14: Feasibility and Viability Of Cops As A Teacher Edumentioning
confidence: 59%
See 2 more Smart Citations
“…As the international educational policy increases expectations for improved educational outcomes, a more comprehensive understanding of teacher professional development experiences that can enhance their knowledge and can support teacher growth and change proves indispensable to policy decision makers and training course designers. Since traditional teacher professional development policies have been largely found to be ineffective, recent research findings confirm that online CoPs with their technological affordances and properly designed implementation schedules have a real potential to be an effective model for the professional development of teachers (Kourkouli, 2018). The present paper provides evidence in the direction of evaluating the effectiveness of this innovative teacher education model and highlighting this perspective in terms of the Coordinators' reports while recognizing their key role.…”
Section: Chart 14: Feasibility and Viability Of Cops As A Teacher Edumentioning
confidence: 59%
“…The implementation of this model in EFL teachers' continuing professional development in Greece took shape in the form of ELTeachers online CoPs set up and officially launched in the academic year of 2014-2015. The investigation of the teachers' participation has confirmed that teachers can benefit from membership in supportive online Communities of Practice and has also provided evidence on the central role that online Communities of Practice can play in the teacher education field in Greece as an effective catalyst for the professional development of teachers (Kourkouli, 2018). Therefore, it is the purpose of this paper to investigate a different aspect, the involvement of the four (4) Greek EFL School Advisors who acted as Coordinators of the four (4) online CoPs under research, training fourty-nine (49) EFL teachers.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The investigation of the teachers' participation has confirmed that teachers can benefit from membership in supportive online CoPs and has also provided evidence on the central role that online CoPs can play in the teacher education field in Greece as an effective catalyst for the professional development of teachers. In addition, the study highlighted specific factors that supported teachers' reflection, their reported reconstruction of beliefs and practices and the reported effectiveness of the training experience in relation to their teaching practice (Kourkouli 2018a). Further research has also confirmed that ELTeachers online CoPs constitute a teacher training model that empowers teacher trainers themselves to engage in "reformed" training practice.…”
Section: Introductionmentioning
confidence: 71%
“…The CoP training schedule and material was based on reported teachers' needs and was given to most Coordinators as a "guidebook" for further development. Coordinators posted one monthly activity in each CoP's forum divided in two fortnight sections with strict deadlines and specific ground rules designed to multiply interaction, foster reflection, development of open discussion, connection with teachers' everyday practice, provision of feedback and open interaction among the participants (Kourkouli, 2018a).…”
Section: Study Contextmentioning
confidence: 99%